Historisasi Kerajaan Turki Utsmani dan Simbol Kebangkitan Umat Islam - Aristan; Abu Haif (Rihlah: Jurnal Sejarah dan Kebudayaan, 2024)
This research aims to reveal aspects of the historicization of the Ottoman Empire as an Islamic empire that once estabilished its glory in the 13century to the 20 century.Trough the historical method, this research uses a historical approach through heuristics (source collection), verification (source criticism), and interpretation (interpretation). The fingdins of this research show that the formation of the Ottoman Empire was rooted in the collapse of Abbasid power due to attacks by the Mongol army. The collapse of Abbasid power than had implications for the political power of Baghdad, wich was the epicenter of Islamic civilization at that time. Baghdad which wa the center of sciense, also collapsed caused (source) Muslims to fall into a deep sleep during yhat time. To awaken Muslims from their slumber, the Turkish nation through the Ottoman Empire began to emerge as a new Islamic power. The Ottoman Empire became the base of Muslim power in Eastern Europa. It can be said that the Ottoman Empire as a historical milestone in the revival of Muslims after the fall of Baghdad. The succes of the kindom was the territorial expansion carried out by the kindoms leaders and their successors. There were several advances in Ottoman Turkey, namely progress in the fields of culture, progress in the military and political fields, and progress achieved in the fields of Islam economic sector.